MEKANISME PEMEROLEHAN BAHASA PADA ANAK USIA SATU DAN LIMA TAHUN - Tussolekha, Rohmah (JURNAL PESONA, 2015)
AbstractIssues addressed in this study are the mechanisms of language acquisition in children ages 1 and 5 years. Based on these problems, this study aimed to describe the mechanisms of language acquisition in children aged 1 year and the mechanisms of language acquisition in children aged 5 years. The method used in this research is a method of descriptions by using a qualitative approach. The samples in this study were children aged one year from Sidoharjo Pringsewu and children five years of age who come from Panjerejo Gading Rejo. Language acquisition data taken through the interview process, observation, and record narration in a straightforward manner. The results showed that in children aged one year, was able to say a few words, though the words are spoken and the child is not yet clear exactly what is being taught in imitating their parents. Daffa (five year olds) at his age already have good language skills. Sentences that conveyed is understood by others. In conversation he was able to use words that connect cause and effect, such as the word